Reviewing the Past and Looking to the Future: Activists Reminisce at the Mine Mill Centennial Conference Sudbury, May 1993 - Buse, Dieter K.; Steedman, Mercedes (Labour / Le Travail, 1994)
The article introduces the edited transcript of sessions of the Mine Mill Centennial Conference held in Sudbury, Ontario, in May 1993. The conference, which commemorated the 100th anniversary of the founding of the Mine, Mill and Smelter Workers' Union, was attended by 200 people including union stewards, academics, labour leaders, and retired workers. The sessions provided a forum for retired activists to reflect on their lifetime of experience in the union movement as well as to address current political concerns. Themes included the union and communism, the union in the community, relations with other unions, women in the labour movement (notably the Mine Mill Women's Auxiliary), political activism, and the path forward for working people and organized labour. Brief biographies of the presenters are also provided.
Keywords: CONFERENCES & conventions; CONGRESSES; LABOR unions -- Congresses; Labor movement; Ontario; SUDBURY (Ont.)